Exploring Batho Pele and Ubuntu Principles in the School Social Work Practice in South Africa: A Narrative Literature Review - Boboyi, Asanda (Journal of Ecohumanism, 2025)
Integrating Batho Pele principles and Ubuntu philosophy provides a culturally relevant and values-driven framework for addressing South African school social work's complex challenges. Grounded in transparency, accountability, and citizen-centred service principles, Batho Pele aligns seamlessly with Ubuntu’s emphasis on interconnectedness, compassion, and mutual respect. Together, these frameworks offer a holistic and transformative approach to reimagining school social work practices in ways that prioritise both individual and community well-being. This conceptual paper employs a narrative literature review to explore the potential correlation between these two frameworks. It thoroughly examines the Batho Pele principles, provides an overview of Ubuntu philosophy and its core tenets, and critically analyses their correlation. The discussion extends to the relevance of these frameworks in addressing the multifaceted demands of school social work, particularly in fostering equity, inclusivity, and social cohesion. Therefore, the paper advocates for a school social work practice that is contextually meaningful and impactful by bridging these principles. Such a practice supports the holistic development of learners and their communities while emphasising the urgent need for a paradigm shift rooted in South Africa’s rich philosophical heritage. This integrated approach aims to create a more equitable, empathetic, and sustainable educational environment.